A STUDY CORRELATION BETWEEN STUDENTS’GRAMMAR MASTERY, THEIR WRITING AND LISTENING COMPREHENSION ACHIEVEMENT - Jamaludin Sanday; Dede Nurdiawati (Indonesian EFL Journal, 2021)
Listening and writing are the challenging skill for EFL learners. It aims to find out the students' problems in listening and writing comprehension through the grammar mastery. The population of this research is 70 students which are divided into three classes. In taking sample from the population, the researchers selected randomly 10 students from each class so there will be 30 students on joining it, mostly they got some problems with grammar and listening also writing. From that case, we try to make a correlation between the listening comprehension and writing achievement through the grammar mastery. From the whole of actions that we had conducted, we have some great result that they have improved their abilities. It is connecting each other. It means that the three variables is strong enough. The conclusion that can be drawn based on the findings of this research is there is positive correlation between students’ grammar mastery and their writing achievement. In other words, the better students’ grammar mastery, the better their writing and listening comprehension achievement will be.Keywords: A study correlation; grammar mastery; writing; listening comprehension